Compilation of Islamic Law and Law No. 35 of 2014 on the Protection of Children Victims of Divorce - Musram Doso; Vina Adania (Journal of Innovative and Creativity, 2025)
Divorce is a growing social phenomenon that affects not only married couples, but also children, who are the most vulnerable parties. Children who are victims of divorce are prone to psychological, social, and emotional disorders due to changes in family structure, lack of parental attention, and post-divorce conflicts. This study aims to analyze the forms of protection for children affected by divorce from the perspective of the Compilation of Islamic Law (KHI) and Law Number 35 of 2014 concerning Child Protection, as well as to determine the implementation of such protection in Bandilan Village, Prajekan District, Bondowoso Regency. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, interviews, and literature studies of relevant laws and regulations and reference sources. The data were analyzed descriptively to describe the factual conditions of the protection of children of divorce in the community. The results showed that parental divorce in Bandilan Village had a significant impact on the psychological condition of children, such as feelings of loss, anxiety, decreased self-confidence, behavioral changes, and a tendency to engage in risky behavior as a form of seeking attention. Although normatively, the KHI and Law Number 35 of 2014 have regulated the obligations of parents and the state in protecting children's rights, their implementation in the field has not been optimal. Lack of parental awareness, post-divorce conflicts, and minimal psychological support are the main factors hindering the effectiveness of child protection. Therefore, cooperation between parents, families, communities, and the government is needed to ensure that children's rights are fulfilled, especially in terms of psychological and emotional protection.